2017
DOI: 10.3168/jds.2016-12139
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of a standardized botanical extract for the prevention of naturally occurring diarrhea in newborn Holstein calves

Abstract: The objectives of this study were to evaluate the prophylactic use of SB-300 (Jaguar Animal Health, San Francisco, CA), a standardized botanical extract isolated from the bark latex of Croton lechleri, on reducing fecal water losses and diarrhea events in Holstein bull calves individually housed under a restricted whole-milk feeding regimen (6 L/d) from 1 to 25 d of life. Fluid therapy administration due to dehydration, average weight gain, and the fecal microbiome were also evaluated. Bull calves used in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Incorporating an appropriate amount of corn silage into cow roughage can significantly enhance feed intake, milk production, and milk protein content [ 9 , 90 , 92 , 93 , 94 ]. Biological feed has the ability to regulate the microflora of ruminant rumen, boost immunity and antioxidant capacity, optimize growth performance, and enhance meat quality; the results are shown in Table 1 [ 54 , 56 , 71 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. Other research has demonstrated that the inclusion of silage in dairy cow diets can enhance their immune function and antioxidant capacity, as well as elevate the levels of polyunsaturated fatty acids present in milk [ 106 ].…”
Section: Application Of Biological Feed In Cattle Breedingmentioning
confidence: 99%
“…Incorporating an appropriate amount of corn silage into cow roughage can significantly enhance feed intake, milk production, and milk protein content [ 9 , 90 , 92 , 93 , 94 ]. Biological feed has the ability to regulate the microflora of ruminant rumen, boost immunity and antioxidant capacity, optimize growth performance, and enhance meat quality; the results are shown in Table 1 [ 54 , 56 , 71 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. Other research has demonstrated that the inclusion of silage in dairy cow diets can enhance their immune function and antioxidant capacity, as well as elevate the levels of polyunsaturated fatty acids present in milk [ 106 ].…”
Section: Application Of Biological Feed In Cattle Breedingmentioning
confidence: 99%
“…Teniendo en su látex rojo sus principios activos, donde podemos recalcar los metabolitos secundarios pertenecientes a diferentes grupos: entre ellos fenoles, terpenoides, alcaloides, leptinas, polepeptidos, siendo uno de ellos la taspina que actúa principalmente en la cicatrización de heridas y poseyendo actividad antiinflamatoria, también tenemos a la proantocianidina SP-303 con su acción antiviral y ciertos compuestos fenólicos como el ácido clorequinico y coberinas A y B, que tienen propiedades antimicrobianas (15,19,23).…”
Section: Introductionunclassified
“…Some alternative treatments for diarrhea have been studied recently, including zinc, crofelemer, lactoferrin, cinnamaldehyde, and bacteriophages targeting enteropathogens (13)(14)(15)(16)(17). Ethnoveterinary or Chinese herbal medicine has become a research hotspot in the clinical treatment of diseases such as calf diarrhea due to its characteristics of fewer side effects, low cost, almost no residue, and no drug resistance (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%